Ecology and seasonality of sandflies and potential reservoirs of cutaneous leishmaniasis in Ochollo, a hotspot in southern Ethiopia. - Myrthe Pareyn; Emma Van den Bosch; Nigatu Girma; Natalie van Houtte; Stefan Van Dongen; Gert Van der Auwera; Fekadu Massebo; Simon Shibru; Herwig Leirs (Public Library of Science (PLoS), 2019)
Background Ochollo is a village in southern Ethiopia burdened with cutaneous leishmaniasis (CL), where Phlebotomus pedifer is the only vector for Leishmania aethiopica and hyraxes are confirmed reservoir hosts. A detailed description of the different players of transmission, and the ecology and seasonality of the vector needs to be established in order to accomplish efficient control programs. Methods and findings Between March 2017 and February 2018, a monthly sandfly collection was carried out in different habitats and records of temperature and humidity were taken. Rodents and hyraxes were trapped in the dry and wet season. All samples were screened for Leishmania kinetoplast DNA (kDNA). Positive samples were further processed for determination of the Leishmania species and the species of the sandfly/small mammal that was found infected. Additionally, the species of 400 sandfly specimens from different habitats and seasons was identified. 17,190 Sergentomyia and Phlebotomus sandflies were caught and showed an overall kDNA prevalence of 2.6%, all were L. aethiopica infections only found in P. pedifer. The overall sandfly and P. pedifer abundance peaked in the dry season and was negatively correlated with the %RH. The kDNA prevalence varied over the months and was negatively correlated with the temperature. Total sandfly abundance did not differ between the sampled habitats, but P. pedifer was the distinct predominant species only in caves. Moreover, significantly more infected sandflies were found in caves. Only 1/192 rodents were kDNA positive, while 20.0% (5/25) of Heterohyrax brucei were found infected. Conclusions This study suggests that caves may be a source of multiplication of the infection. If an outdoor control program would be considered, it would be useful to focus on caves in the wet season, when the sandfly abundance is lowest. The captured rodent species appear not important for transmission and the contribution of hyraxes in transmission should be further investigated.